The influence of socio-demographic factors and risky lifestyles on the criminal victimisation of students : the case of a Kenyan University - Kariuki, Peterson Mwai; Barkhuizen, Merlyn (African Perspectives of Research in Teaching & Learning (APORTAL), 2023)
Unlike crimes committed against tourists or police officers, the annual crime statistics released by the Kenya National Police Service do not reflect crimes committed against university students per se. While there is substantial evidence on the extent and characteristics of criminal victimisation in the general population, as well as among university students in America and the West, evidence on this subject in Sub-Saharan Africa is drawn from limited studies. To date, the extent and characteristics of criminal victimisation among university students in Kenya are yet to be examined. While using a quantitative approach and a survey research design, a sample size of 1717 respondents was randomly computed from a population of 17167 individuals at a peri-urban university, west of Kenya, to determine the relationship between victimisation and socio-demographic factors and risky lifestyle exposure characteristics. Findings indicate that socio-demographic variables such as age, marital status, employment status, and residence were significantly related to victimisation. Additionally, risky lifestyle activities such as frequenting bars, socialising with strangers, partying on and off campus, and abusing bhang (a derivative of cannabis) and alcohol were significantly related to victimisation. To reduce student victimisation, we recommend the design of effective victimisation reduction advertisements and investment in on-campus housing.
Journal article published in Africa Perspectives of Research in Teaching in Learning (APORTAL) Vol 7 (1) (2023)
Keywords: Lifestyle exposure; Risk; Socio-demographic factors; Victimisation; University students; College students -- Kenya; Victims of crimes surveys; Criminals -- Kenya; Crime -- Kenya